Psikolojik danışmanların mesleki doyum düzeylerinin yıldırma, psikolojik sağlamlık ve örgütsel bağlılık açısından incelenmesi - Kavsara, Reyhan (My University, 2024)
Bu araştırmanın hedefi, psikolojik danışmanların mesleki doyum seviyelerinin nasıl etkilendiğini, özellikle yıldırma, psikolojik sağlamlık ve örgütsel bağlılık faktörleri açısından değerlendirmektir. İlişkisel tarama yöntemi kullanılarak yapılan bu çalışma, psikolojik danışmanların iş tatminleri ve bu değişkenler arasındaki ilişkileri belirlemeyi amaçlamaktadır. Araştırma katılımcıları, İstanbul'da çalışan toplam 434 psikolojik danışmanı içermekte olup, bunların %80'i kadın (347), %20'si ise erkek (87) olarak kaydedilmiştir. Araştırma verileri, çevrimiçi oluşturulan formlar aracılığıyla toplanmıştır. Veri toplama araçları arasında kişisel bilgi formu, negatif davranışlar ölçeği, örgütsel bağlılık ölçeği, kısa psikolojik dayanıklılık ölçeği ve iş tatmini ölçeği bulunmaktadır. Bu ölçeklerin güvenilirlik analizleri yapılmış ve Cronbach Alpha katsayıları hesaplanarak ölçeklerin yüksek derecede güvenilir olduğu tespit edilmiştir. Veriler, IBM SPSS Statistics 22 ve AMOS v21 programları kullanılarak analiz edilmiş, çeşitli istatistiksel testler uygulanmıştır. Araştırma bulgularına göre, yıldırma ile iş tatmini arasında örgütsel bağlılık düzenleyici bir rol oynarken, psikolojik dayanıklılığın bir etkisi gözlemlenmemiştir. İş tatmini, örgütsel bağlılık ve psikolojik dayanıklılık arasında pozitif yönde anlamlı ilişkiler saptanmıştır. Demografik değişkenler açısından yapılan analizler, cinsiyet ve çalışılan kurum türüne göre iş tatmininde anlamlı farklılıklar göstermemiştir, ancak mesleki deneyim süresiyle iş tatmini arasında farklar belirlenmiştir.

The objective of this study is to examine the levels of job satisfaction among psychological counselors, particularly in relation to mobbing, psychological resilience, and organizational commitment. Utilizing a relational survey model, this research aims to elucidate the relationships between counselors' job satisfaction and these variables. The study's participants comprised a total of 434 psychological counselors working in Istanbul, with 347 women (80%) and 87 men (20%). Data for this research were collected via online forms. Instruments utilized in the study include a personal information form, a negative acts questionnaire, an organizational commitment scale, a brief resilience scale, and a job satisfaction scale. Reliability analyses were conducted for these scales, and Cronbach's Alpha coefficients were calculated, confirming that the scales are both valid and highly reliable. Data were analyzed using IBM SPSS Statistics 22 and AMOS v21 software, employing various statistical methods such as descriptive statistics, Independent Samples T-Test, One-Way ANOVA, and structural equation modeling. Findings from the study indicate that while organizational commitment plays a moderating role in the relationship between bullying and job satisfaction, no significant moderating effect of psychological resilience was observed. There were significant positive relationships between job satisfaction, organizational commitment, and psychological resilience levels. Additionally, the analyses exploring demographic variables (gender, age, professional experience, type of institution worked for, etc.) revealed no significant differences in job satisfaction based on gender or the type of institution. However, there were differences in job satisfaction related to the duration of professional experience. It can be stated that those with 11-15 years of experience reported lower job satisfaction compared to those with 1-5 years and 6-10 years of experience. No significant differences in job satisfaction were found based on educational level. Among the various age groups, counselors aged 36-40 reported lower job satisfaction compared to those in the 26-30, 31-35, and over 40 age ranges. Regarding marital status, unmarried counselors reported lower job satisfaction compared to their married and divorced peers.
Investigation of the job satisfaction levels of psychological counselors in terms of mobbing, psychological resilience and organizational commitment
Keywords: İş tatmini; Job satisfaction; mesleki doyum; mobbing; organizational commitment; örgütsel bağlılık; Psikolojik danışmanlık ve rehberlik; psikolojik sağlamlık; Psychological counseling and guidance; psychological resilience; yıldırma job satisfaction